Analisis Minat belajar Siswa pada Pembelajaran Bahasa Indonesia di kelas VI SD Negeri 104202 Bandar Setia, Kecamatan Percut Sei Tuan - Alfajra Muliaty Puteri Zein; Rani Rosaria Tinambunan; Rosvelly R Hutasoit; Sarah Pratiwi (Universitas Muhammadiyah Enrekang, 2023)
The purpose of this study was to find out how students' interest in participating in Indonesian language learning and find out how the implementation of Indonesian language learning media was carried out by teachers in class VI SD Negeri 104202 Bandar Setia, Percut Sei Tuan District, Deli Serdang Regency, North Sumatra. The Data Collection Technique is a quantitative analysis technique and is objective through collecting data based on a questionnaire. The research method used is a quantitative survey method, which uses a questionnaire as an instrument in receiving information. Survey research method, this is done by conducting surveys or collecting data directly from research respondents. Usually surveys are carried out by distributing questionnaires or questionnaires as the data collection instrument. This questionnaire or questionnaire is distributed to respondents who have been determined as the research sample.